(untitled) (Social Security Management Journal, 2025)
Safety performance is extremely important in a military context as it directly affects the protection of soldiers and the successful completion of missions. This study aims to examine military safety performance through a combination of scientometric and scoping review methods. The research emphasizes the crucial roles played by safety leadership, culture, and technological advancements. To analyze the data, bibliographic databases such as Scopus and WoS were examined, and advanced data analysis tools like ScientoPy and VOSviewer were used for data processing and visualization. The analysis produced a list of the top ten keywords including safety, safety standards, safety performance, safety culture, software safety, military, flood risk, risk assessment, laser safety, and safety measures. These keywords highlight the impact of effective safety leadership on soldiers’ perception of risk and operational success, as well as the importance of technologies like smart wearables for monitoring health and location. The study also identifies various stressors that affect safety such as job burnout and PTSD and emphasizes the need for targeted interventions. The scientometric analysis shows a growing interest in academic research on military safety performance, while the scoping review identifies gaps in current studies and suggests areas for future research. By integrating continuous training, technological advancements, and adaptive leadership, the study proposes a comprehensive approach to improve military safety and operational effectiveness. The findings underscore the importance of cultivating a strong safety culture and the need for ongoing research to address the evolving challenges in military environments.